Plataformas streaming ante la construcción de notas tendencias de índole nacional - Vélez Escobar, Gema Tatiana (2020)
The present study seeks to analyze the Streaming Wambra platform and its impact on the construction of national trend notes. Case study: National Unemployment - Decree 883, in which it is proposed to know how to determine the theoretical foundations that support the research project, in addition to identifying the form of publication of information on the Wambra digital platform through statistics and measurement metrics between on October 03 and 13, 2019 and for establishing the role of digital media compared to traditional media during the eleven days of stoppage. For which a documentary type methodology was proposed, an explanatory level and a qualitative and quantitative approach, for which the interview and survey techniques were applied. According to the results of the analysis, the contents issued by the Wambra digital platform between October 03 and 13, 2019 were 26 publications on its website, 65 publications on Facebook, 272 Twitter and 36 publications on Instagram. Noting that on Facebook and Twitter users had more interaction, unlike other networks……….